Ultrastructure of thyrocytes, assessment of their functional state after prolonged exposure to sodium benzoate and simulation of bone fractures and justification for the effectiveness of mexidol and selenase - Vitalii N. Morozov (Наука и инновации в медицине)
Aim – to study the effect of a 60-day exposure to sodium benzoate and a defect in the tibiae on the ultrastructure and functional state of rat’s thyroid gland thyrocytes and substantiate the effectiveness of mexidol and selenase.